2005
DOI: 10.1021/es0501767
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Steroid Estrogens in Australian Inland and Coastal Wastewater Treatment Plants

Abstract: Environmental Science and Technology (Revised version January 2005): note also CORRECTION published in EST 39(18): 7344* Corresponding author: Phone +61 2 9385 5082, fax: +61 2 9313 8624, email: andrew.feitz@unsw.edu.au AbstractA comparison of estrone (E1), 17β-estradiol (E2) and 17α-ethinylestradiol (EE2) removal at a coastal enhanced primary and inland advanced sewage treatment plant (STP) is reported. The average concentration of estrogens in the raw sewage is similar to reports in other studies. The sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(72 citation statements)
references
References 54 publications
3
65
1
3
Order By: Relevance
“…This is consistent with work by Leusch et al (2006), who also found that secondary treatment was the most effective treatment step to remove oestrogenic and androgenic activity from sewage water with removal of up to 99% using activated sludge treatment. Braga et al (2005a) investigated the activated sludge process for the removal of oestrogens in a STP in Western Sydney and found 85% removal for oestrone and 96% removal for 17b-oestradiol.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with work by Leusch et al (2006), who also found that secondary treatment was the most effective treatment step to remove oestrogenic and androgenic activity from sewage water with removal of up to 99% using activated sludge treatment. Braga et al (2005a) investigated the activated sludge process for the removal of oestrogens in a STP in Western Sydney and found 85% removal for oestrone and 96% removal for 17b-oestradiol.…”
Section: Resultsmentioning
confidence: 99%
“…Effluent discharge from industrial and domestic waste treatment plants, leaching of bio-solids in landfills and sludge, and recycled water used in agriculture are among the most common ways that such pollutants enter the environment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A negligible mass load of estrogens absorbed onto sludge has been reported previously. 19,42,44 The results suggested that the hormones in the wastewater were efficiently removed/transformed by biodegradation. High biodegradation rate of estrogens, especially in aerobic condition has been extensively reported in the literature.…”
mentioning
confidence: 96%
“…These results fell into ranges reported in the literature. 13,15,18,19,29,39,[42][43][44][45] The PCPs were ubiquitously detected in the wastewater samples (Fig. 2b, Table S1 ‡).…”
mentioning
confidence: 97%